Compare Value at Risk and Return of Assets Portfolio Stock, Gold, REIT, U.S. & Iran Market Indices - Ghorashi, Felor; Darabi, Roya (Asian Journal of Economic Modelling, 2016)
Nowadays investors follow investment in asset like, stocks, gold, and real-estate investment trusts in the world. This study surveys three types of main assets portfolio of stock, gold, and REIT. This article use from S&P500, Gold price, S&P United States REIT of U.S as a development and Iran stock market, Gold price as an emerging country. Samples are collected from 2004 to2014 daily index U.S market and Iran market for 10 years. In this case, we use GARCH model for estimating return and variance with conditional variation. Then use Mont carol simulation for determination Value at Risk with three likelihood. Then calculate correlation of portfolios with multiple regression. Finally, compared Value at Risk and return and correlation for each portfolio (four types of portfolios). Then compare different type of portfolio and select best portfolio via R-Sharp criteria.